Lack of Association Between DJ-1 Gene Promoter Polymorphism and the Risk of Parkinson’s Disease - He, Lu; Lin, Suzhen; Pan, Hong; Shen, Ruinan; Wang, Mengyan; Liu, Zhihao; Sun, Shiyao; Tan, Yuyan; Wang, Ying; Chen, Shengdi; Ding, Jianqing (Frontiers in Aging Neuroscience, 2019)
Low DJ-1 protein level caused by DJ-1 gene mutation leads to autosomal recessive Parkinson’s disease (PD) due to impaired antioxidative activity. In sporadic PD patients, although mutations were rarely found, lower protein level of DJ-1 was also reported. Dysregulation of DJ-1 gene expression might contribute to low DJ-1 protein level. Since promoter is the most important element to initiate gene expression, whether polymorphisms in DJ-1 promoter result in the dysregulation of gene expression, thus lead to low protein level and cause PD is worth exploring. DJ-1 promoter region was sequenced in a Chinese cohort to evaluate possible links between DJ-1 promoter polymorphisms, PD risk and clinical phenotypes. Related information in existing GWAS database were looked up, meta-analysis of the present study and other previous reports was conducted, and expression quantitative trait loci (eQTL) analysis was performed to further explore the association. Three single nucleotide polymorphisms (SNPs) (rs17523802, rs226249 and rs35675666) and one 18bp deletion polymorphism (rs200968609) were observed in our cohort. However, there was no significant association between the four detected polymorphisms and the risk of PD either in allelic or genotype model, in single-point analysis or haplotype analysis. Searching results in genome-wide association studies (GWAS) meta-analysis database PDGene and meta-analysis of this study and previous reports also showed no significance. In addition, eQTL results in GTEx database demonstrated the lack of association between the four polymorphisms and normal human brain DJ-1 expression level, which further confirmed our results. Thus, DJ-1 promoter polymorphisms may play little role in dysregulation of DJ-1 expression and PD susceptibility, low protein level of DJ-1 may be caused by other reasons.